2017
DOI: 10.4103/aam.aam_34_16
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal sepsis in a Nigerian private tertiary hospital: Bacterial isolates, risk factors, and antibiotic susceptibility patterns

Abstract: Background/Objectives:Neonatal sepsis is an important cause of morbidity and mortality in the pediatric age group in spite of several attempts at mitigating its effects. This article determines the prevalence of neonatal sepsis and the pathogens responsible for sepsis as well as risk factors and outcome at the Babcock University Teaching Hospital.Methods:A retrospective analysis of laboratory records of consecutive babies delivered within and outside our hospital suspected of having sepsis over a 1-year period… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
45
5
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(60 citation statements)
references
References 24 publications
9
45
5
1
Order By: Relevance
“…Only few studies reported use of Etest 72,73,106,107 or microdilution 59 on all or some isolates. Several established guidelines for resistance interpretation were referenced: Clinical and Laboratory Standards Institute (CLSI; 36 stu dies), 24,31,36,56,59,63,70,72,73,84,[86][87][88]93,96,99,103,106,[108][109][110][111][112][113][114][115][116][117][118][119][120][121][122][123][124][125] EUCAST, 107 British Society for Antimicrobial Therapy, 60,61,71,97 and French Society of Microbiology. 91 Only 12 (15%) of 81 observational studies provided context by describing the pathway of neonatal presentation.…”
Section: Resultsmentioning
confidence: 99%
“…Only few studies reported use of Etest 72,73,106,107 or microdilution 59 on all or some isolates. Several established guidelines for resistance interpretation were referenced: Clinical and Laboratory Standards Institute (CLSI; 36 stu dies), 24,31,36,56,59,63,70,72,73,84,[86][87][88]93,96,99,103,106,[108][109][110][111][112][113][114][115][116][117][118][119][120][121][122][123][124][125] EUCAST, 107 British Society for Antimicrobial Therapy, 60,61,71,97 and French Society of Microbiology. 91 Only 12 (15%) of 81 observational studies provided context by describing the pathway of neonatal presentation.…”
Section: Resultsmentioning
confidence: 99%
“…Neonatal sepsis is a systemic inflammatory response caused by bacterial production of toxins after gaining entry into the bloodstream and multiplying [1]. It is classified into the early-onset neonatal sepsis (≤ 72hrs) due to bacteria acquired before or during delivery, and lateonset neonatal sepsis (>72 hrs-28days) involving pathogens acquired after delivery [2,3]. Generally, it is a life-threatening case.…”
Section: Introductionmentioning
confidence: 99%
“…This varies based on geographical location, antibiotic usage, time of onset of illness and the use of intravascular medical devices. Globally, about 40% of deaths in children under five from developed and developing countries occurs in the neonatal period (≤ 28 days) with predominance in developing and low-income countries [2]. Empirical treatment according to the World Health Organization is recommended for neonates having sepsis in areas of sub-Saharan Africa that lacks wellequipped microbiology laboratory [6].…”
Section: Introductionmentioning
confidence: 99%
“…17 The similar results were from a different study showing Coagulase-negative Staphylococci (CONS), Staphylococcus aureus and Klebsiella pneumoniae the most common pathogens. 18 These unsimilar studies signify the presence of different organisms in different areas. Results of a similar study showed Klebsiella pneumonia in 25%, Enterobacter in 12.5%, Group B Streptococcus in 12.5% neonates.…”
Section: Section: Pathologymentioning
confidence: 99%